An Analysis of the Merdeka Curriculum's Implementation at Madrasah Ibtidaiyah - Januartini, Dwi; Sari, Theresia Ratna; Tahrun, Tahrun (Jurnal Basicedu, 2024)
The Indonesian government implemented the learner-centered Merdeka Curriculum to overhaul the country's educational system. This curriculum is being used at MI Hijriyah II Palembang, a well-known Islamic elementary school in Palembang. The purpose of this study is to evaluate the Merdeka Curriculum's implementation at MI Hijriyah II Palembang, with an emphasis on its advantages, disadvantages, opportunities, and threats. In order to collect data for this qualitative study, semi-structured interviews, observations, and document analysis were used in conjunction with a case study design. Teachers, students, and administrators from the school were among the participants. The study shows that a learner-centered approach, greater student autonomy, and integration of Islamic values are characteristics of MI Hijriyah II Palembang's Merdeka Curriculum implementation. Still, there are issues like poor training for teachers, a lack of resources, and mistrust from parents. This study highlights the opportunities and difficulties the school faced in implementing the Merdeka Curriculum in a particular educational setting. The results have implications for stakeholder engagement, resource allocation, and teacher professional development, which will ultimately help MI Hijriyah II Palembang and other schools improve how they implement the curriculum